1888 Md. Laws 1379 - (:unkn) unknown (My University, 1886)
§ 280: It shall be lawful to shoot teal ducks, mallards, black ducks, bald pates, and all other ducks known as marsh ducks, in any manner other than by swivel, gun or big gun, from one hour before sunrise until one hour after sunset every day, from the fifteenth day of August to the first day of October of each year, on the waters of the Chesapeake bay, lying and being within the bounds prescribed by section 278.
Keywords: HUNTING REGULATION